IMPLIKASI PENGEMBANGAN PEMBANGUNAN INFRASTRUKTUR KAWASAN JALAN BARU MUARO – AIR MANIS TERHADAP TATA RUANG DI KELURAHAN BUKIT GADO-GADO KOTA PADANG - Erwin Idris Pratama Nasution; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aimed to find out the implications of the development of the new Muaro – Air Manis Road Infrastructure Development for Spatial Planning in Bukit Gado-Gado Village, Padang City. This study used qualitative approach that produced descriptive data with the intention of conducting research, describing, and analyzing the implications of the development of the Jalan Baru Muaro Infrastructure Development Area – Air Manis Against Spatial Planning in Bukit Gado-Gado Village, Padang City. Data was collected through interview, observation and documentation study. In this study the analyzed data were obtained from interviews and interpreted qualitatively in the form of abstractions, words and statements. The results of the study showthe implications of infrastructure development in the area of Baru Muaro Street - Air Manis for spatial planning in the district of Gado-Gado Hill, Padang City. The implementation of infrastructure development has been carried out in accordance with the spatial strategy carried out covering 3 things, namely : (1) consistent cultural control, (2) strengthen economic base, (3) forming an efficient development unit, but in the implementation there are stil some obstacles faced by both internal and external constraints. The efforts made by the government to marginalize the existing constraints is include in increasing people's understanding of Local Regulation (Perda) No. 4 of 2012 concerning RTRW through socialization and intercession, also increasing infrastructure development in the layout area of Gado-Gado Hill.